Turkish Validity and Reliability Study of Humanistic Practice Ability of Nursing Scale - Yanmis, Safiye; Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz (Wiley, 2022)
Background. Nurses should have humanistic qualities to identify what the patient needs with an effective care plan and meet these needs. The aim of this study is to conduct the Turkish validity and reliability study of the Humanistic Practice Ability of Nursing Scale. Methods. This methodological study was carried out with 300 nurses online (e-mail, WhatsApp, Facebook, and Instagram) between April 02, 2021, and May 15, 2021. A questionnaire prepared via docs.google.com/forms was sent to the nurses. The scale was translated into Turkish, and then, the content and construct validity of its Turkish version was obtained through exploratory factor analysis and confirmatory factor analysis. The reliability of the scale was tested by performing item analysis and internal consistency analysis. Results. The analysis revealed that the content validity index of the scale was 0.96. In the exploratory factor analysis performed within the scope of the Turkish adaptation of the scale, the rate of the total variance explained was 59.63%. Factor loadings of all the items ranged between 0.47 and 0.79. While Cronbach's Alpha value was 0.93 for the overall Humanistic Practice Ability of Nursing Scale, it ranged from 0.71 to 0.89 for its subscales. The exploratory factor analysis and confirmatory factor analysis revealed no necessity of making any revision or modification in the scale. Therefore, the 29-item and five-dimension structure of the Humanistic Practice Ability of Nursing Scale was used in its Turkish version. Goodness-of-fit index values were obtained after the CFA was performed. Conclusion. The Turkish version of the Humanistic Practice Ability of Nursing Scale can be used as a valid and reliable measurement tool to assess nurses' humanistic practice ability.
Keywords: Care; Model